Use of combined injection therapy with chondroprotectors for relief of patellofemoral pain syndrome in sportsmen after enteral cross-ligament reconstruction - V. V. Arkov; A. A. Dmitriev; P. Yu. Ershov; O. V. Kuznetsov; O. N. Milenin (Лечащий Врач, 2021)
Enteral cross-ligament (ACL) injury and patellofemoral pain syndrome are important problems of sport medicine. Inflammation plays an important role in pathogenesis of osteoarthritis after sport injuries. The influence of injection therapy with multiagent chondroprotectors on functional state and pain level of sportsmen after the ECL reconstruction was studied. Use of multi-agent chondroprotective therapy in structure of rehabilitation program decreased pain level and improved functional state of patellofemoral joint of sportsmen after the ECL reconstruction.